TRAFFIC LIGHT CONTROL METHOD AND SYSTEM BASED ON URBAN TRUNK LINE VEHICLE QUEUING LENGTH - LIU, Kai; TIAN, Jun; ZHANG, Xingzi; NING, Erwei; ZHANG, Mengmeng; WANG, Shuaiqi; ZHANG, Yingying; WANG, Qi; LI, Jian; FENG, Haixia (2022)
A traffic light control method and system based on urban trunk line vehicle queuing length. The method comprises: calculating the maximum queuing length of vehicles on a straight-going lane in a straight-going red light period according to an initial traffic light period, the straight-going red light period referring to the time length from a straight-going red light turn-on moment to a straight-going green light turn-on moment; according to the maximum queuing length of the vehicles on the straight-going lane in the straight-going red light period, calculating a passing duration required for reaching the number of vehicles in the straight-going green light period, the straight-going green light time period referring to the time length from the straight-going green light turn-on moment to the straight-going green light turn-off moment; according to the passing duration required for reaching the number of vehicles in the straight-going green light time period, a passing duration required for the queuing vehicl